The effect of synbiotics supplement on alcohol use disorders identification test and biochemical parameters, gamma glutamyl transferase, lipopolysaccharide and immunoglobulin a levels, in high risk alcoholics - Sirisapsombat, Vachrintr; Pratummas, Parama; Phucharoen, Phuttharaksa; Nararatwanchai, Thamthiwat; Chaiyasut, Chaiyavat; Sirilun, Sasithorn; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Alcohol consumption does not result in dependence or abuse among most people. Nevertheless, a significant group of the population as a whole unavoidably is troubled by chronic alcoholism.Alcohol is involved in a number of diseases, disorders, and injuries, and several social problems. Aims and Objective: To investigate the possible effects of synbiotics supplement affecting to gut-brain axis in high risk alcohol drinkers through alterations between improving of gut related parameters and changes of alcohol use disorders identification test (AUDIT). Materials and Methods: Single group, pre- and post-test study. Participants: 24 male patients, alcohol use disorders identification test at 8 or above. Exclusions included clinical diagnosis of cirrhosis, immunodeficiency, autoimmune disorder, use of drugs other than alcohol, pregnancy and lactation, use of antibiotics and herbs during the course of study. Intervention: Synbiotics containing probiotics 7 species and prebiotic 3 types once a day before bedtime for 8 weeks. Main outcome measures: Primary outcome- the efficacy of synbiotics supplement improving subjective AUDIT score. Secondary outcome- changes on gut related biochemical parameters (lipopolysaccharide and immunoglobulin A levels). Results: Twenty high risk alcoholic subjects (with an average age of 46.14 ± 18.34 years) were supplemented with synbiotics contained 25 billion cells of probiotics per day for 8 weeks. After the end of intervention, there was significantly improved total AUDIT score (p=0.001). The changes in gamma glutamyl transferase (GGT), lipopolysaccharide and immunoglobulin A level was calculated. GGT (from 90.62 ± 56.65 U/l to 67.67 ± 57.00 U/l), lipopolysaccharide (from 23.19 ± 9.57 to 16.67 ± 4.52 mg/ml) and immunoglobulin A (from 377.13 ± 229.88 to 484.16 ± 290.98 ng/ml) levels were significantly changed when compared to the baseline value. Conclusion: The results of the current study suggested that the consumption of synbiotics significantly improved subjective and objective parameters in high risk alcoholic patients, and further studies are mandatory to reveal the effects of synbiotics on gut health link to central neurological system.